Perioperative glycemic status is linked to postoperative complications in non-intensive care unit patients with type-2 diabetes: a retrospective study. (May 2022) - Oba, Takeshi; Nagao, Mototsugu; Kobayashi, Shunsuke; Yamaguchi, Yuji; Nagamine, Tomoko; Tanimura-Inagaki, Kyoko; Fukuda, Izumi; Sugihara, Hitoshi
Background: Perioperative hyperglycemia is a risk factor for postoperative complications in the general population. However, it has not been clarified whether perioperative hyperglycemia increases postoperative complications in patients with type-2 diabetes mellitus (T2D). Therefore, we aimed to analyze the relationship between perioperative glycemic status and postoperative complications in non-intensive care unit (non-ICU) hospitalized patients with T2D. Materials and Methods: Medical records of 1217 patients with T2D who were admitted to the non-ICU in our hospital were analyzed retrospectively. Relationships between clinical characteristics including perioperative glycemic status and postoperative complications were assessed using univariate and multivariate analyses. Perioperative glycemic status was evaluated by calculating the mean, standard deviation (SD), and coefficient of variation (CV) of blood glucose (BG) measurements in preoperative and postoperative periods for three contiguous days before and after surgery, respectively. Postoperative complications were defined as infections, delayed wound healing, postoperative bleeding, and/or thrombosis. Results: Postoperative complications occurred in 139 patients (11.4%). These patients showed a lower BG immediately before surgery ( P = 0.04) and a higher mean postoperative BG ( P = 0.009) than those without postoperative complications. There were no differences in the other perioperative BG parameters including BG variability and the frequency of hypoglycemia. The multivariate analysis showed that BG immediately before surgery (adjusted odds ratio (95% confidence interval [CI]), 0.91 (0.85–0.98), P = 0.01) and mean postoperative BG (1.11 (1.05–1.18), P < 0.001) were independently associated with postoperative complications. Conclusion: Perioperative glycemic status, that is, a low BG immediately before surgery and a high mean postoperative BG, are associated with the increased incidence of postoperative complications in non-ICU patients with T2D.